2016
DOI: 10.1513/annalsats.201605-356aw
|View full text |Cite
|
Sign up to set email alerts
|

The Lung Microbiome and Airway Disease

Abstract: A growing body of literature has demonstrated relationships between the composition of the airway microbiota (mixed-species communities of microbes that exist in the respiratory tract) and critical features of immune response and pulmonary function. These studies provide evidence that airway inflammatory status and capacity for repair are coassociated with specific taxonomic features of the airway microbiome. Although directionality has yet to be established, the fact that microbes are known drivers of inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Normal gut microbiome inhibits systemic IgE responses through signals directed to toll‐like receptors of innate immune cells including mast cells and basophils, while the production of short‐chain fatty acids modulates dendritic cell responses . In patients with CF, deteriorating lung function is associated with decreased phylogenetic variety of the bacterial airway microbiome and enrichment in pulmonary pathogenic genera such as Staphylococcus aureus, Pseudomonas aeruginosa, Haemophilus influenza , and Burkholderia cepacia . The proportion of saprophytic fungal species, which is <0.1% under normal conditions, is increased in CF patients’ mycobiome and following antibiotic regimens .…”
Section: Aspergillus Fumigatus and Its Interaction With The Human Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal gut microbiome inhibits systemic IgE responses through signals directed to toll‐like receptors of innate immune cells including mast cells and basophils, while the production of short‐chain fatty acids modulates dendritic cell responses . In patients with CF, deteriorating lung function is associated with decreased phylogenetic variety of the bacterial airway microbiome and enrichment in pulmonary pathogenic genera such as Staphylococcus aureus, Pseudomonas aeruginosa, Haemophilus influenza , and Burkholderia cepacia . The proportion of saprophytic fungal species, which is <0.1% under normal conditions, is increased in CF patients’ mycobiome and following antibiotic regimens .…”
Section: Aspergillus Fumigatus and Its Interaction With The Human Hostmentioning
confidence: 99%
“…However, the first two stages lack consensus definitions. The growth of A. fumigatus in the airways, also termed “carriage” or “colonization,” may be evidenced by culture‐based methods, galactomannan detection in bronchoalveolar lavage liquid, PCR assays, and more recently new‐generation sequencing methods and antigenemia measures . The detection of “precipitins,” which comprise mainly but not exclusively IgG, or anti‐ A. fumigatus ‐specific IgG, is sometimes considered as indicative of A. fumigatus carriage, but most teams distinguish genuine A. fumigatus colonization from anti‐ A. fumigatus IgG detection.…”
Section: Aspergillus Fumigatus and Its Interaction With The Human Hostmentioning
confidence: 99%
“…In addition, another study in young children found a significant relationship between wheezy episodes and Haemophilus influenzae and Moraxella catarrhalis, but on the other hand, Streptococcus pneumoniae was not found to have a significant association with recurrent wheeze. 43 The PARSIFAL and GABRIELA studies revealed the protective effect of childhood exposure to multiple and diverse microbial communities against asthma.4 4 Exposure to a wide array of microorganisms in the farming environment can lead to activation of Toll-like receptors, with subsequent set-off of their respective signaling pathways and a resulting increase in activation of type 1 helper T cells. 44 This can lead to reduced action of the type 2 helper T cell, which is distinctively found in asthma.…”
Section: Asthmamentioning
confidence: 99%
“…3 The respiratory tract is in constant contact with the external environment and the microbial load it harbors is higher in the upper airways and significantly reduced in the lower airways. 4 Apart from ethical and practical difficulties surrounding clinical studies involving newborns, sampling difficulty, contamination and low bacterial biomass are added challenges to surmount. 5 This review focuses on the newborn respiratory microbiome and its potential causality in pulmonary diseases in neonates.…”
mentioning
confidence: 99%
“…Dysbiosis of intestinal microbiota is involved in the pathogenesis of chronic bowel diseases including chronic inflammatory bowel diseases (IBD), ulcerative colitis (UC), and Crohn's disease (CD) (Macfarlane et al, 2009;Matsuoka and Kanai, 2015). Recently, the lung microbiota was also suggested to contribute to lung disease, and the changes of the lung microbiota will affect the risk of disease, the response to drugs, and the clinical outcomes (Lynch, 2016). There are many factors, such as anatomical injuries, pathological effects, physiological changes, and immune system defects, which could disrupt the lung microbiota and result in chronic lung diseases .…”
Section: The Microbiota In Lung Diseasementioning
confidence: 99%